The Mediation Effect of Social Connectedness Between Big Five Personality Traits and Social Interaction Anxiety Among Third Culture Kids in Bangkok - Zainab, Syeda Affifa; Mohanan, Dr. Santhosh Ayathupady (Scholar: Human Sciences, 2021)
The study examined the association of social interaction anxiety (SIA), social connectedness (SC) and the big five personality traits in third culture kids in Bangkok. The purpose of the current study was to investigate the direct and indirect effect of the Big Five traits on SIA in TCKs, mediated by SC. The study employed Path Analysis via a set of multiple regressions for each of the five traits and Process Analysis to test the significance of mediation effect. A convenience sample of 123 TCKs, 78 girl and 45 boys of age 14-18 years, from the international school in Bangkok filled out questionnaire of Social Interaction Anxiety Scale (SIAS), Social Connectedness Scale-revised (SCS-R) and Big Five Inventory (BFI). Results showed that extroversion was a significant negative predictor with a direct and indirect effect on SIA, partially mediated by SC (β = -.19, 95% CI = -.33, -.09). Neuroticism was a significant positive predictor with a direct and indirect effect on SIA, partially mediated by SC (β = .21, 95% CI = .11, .32). Openness, conscientiousness and agreeableness showed no significant direct or indirect effect on SIA. Its shows that low sense of belonging and connection in introverted and neurotic adolescents exacerbates their concerns in social interactions, thus contributing towards making them socially anxious. Therefore, adolescent TCKs with low extroversion and high neuroticism can be protected against their natural vulnerabilities towards social interaction anxiety with the help of developing higher levels of social connectedness.